Distributed preservation services: integrating planning and actions - Becker, Christoph (2008)
Digital preservation has turned into an active field of research. The most prominent approaches today are migration and emulation; especially considering migration, a range of working tools is available, each with specific strengths and weaknesses. The decision process on which actions to take to preserve a given set of digital ob jects for future access, i.e., preservation planning, is usually an ad-hoc procedure with little tool support and even less support for automation. This paper presents the integration of tools and services for object migration and characterization through a service oriented architecture into a planning tool called Plato, thus creating a distributed and highly automated preservation planning environment.